Structural Behaviour of Interlocking Hollow Block Panel With Stiffener Subjected to Axial And Eccentric Load - A. Shehab, Fares (2005)
The search for more rapid construction that need ordinary labor has led to the development of interlocking masonry system in which the walls can be assembled without using any mortar layer. The assembled hollow blocks in the wall provide continuous hollow voids, which can be used to host stiffeners in vertical and horizontal directions to enhance the integrity of the wall. However the effects of reinforced concrete stiffeners on the structural response of the interlocking walls are still not known and require further investigation. This research is mainly focused on the structural behavior of interlocking hollow block walls with stiffener constructed using PUTRA interlocking hollow block under axial and eccentric vertical load. Experimental program includes testing of individual block units, interlocking prism and full scale interlocking walls. Since the compressive capacity of a wall is defined in terms of compressive strength of the block unit used to construct the wall, the compressive strength of different individual block unit was evaluated by testing 40 block units for each type of block used to assemble the wall stretcher ,half and comer block units. Furthermore three course grouted prisms were tested and compared with un-grouted prisms to explore the effect of grout on prism strength; these results were compared with results presented by other researchers. Five wall specimens of 1.2 m width and 3.0 m height were tested under the effect of axial and eccentric vertical loads considering different eccentricity of 40 and 55 mm. The research aims to investigate the effect of two different stiffeners layout on their structural response compared to the walls without stiffener highlighting the difference between interlocking walls with stiffener and conventional bonded masonry walls using mortar layers. In the first layout, the reinforced concrete (R.C.) stiffeners were located at the perimeter of wall, while in the second layout the stiffeners were located at wall perimeter as well as horizontal stiffeners at mid height of wall. The structural responses of tested panels were monitored in terms of wall efficiency, deformation characteristics strain distribution reduction in wall capacity due to effect of eccentric load cracking and failure mode. The testing results show that the presence of stiffeners has improved the behavior of tested panels by increasing the load carrying capacity of stiffened panels by 15% to 30% compared to un-stiffened specimens. Furthermore the horizontal stiffener located at mid height of wall plays important roles in the capacity of wall and its failure mode.